Decreased cervical cancer cell adhesion on nanotubular titanium for the treatment of cervical cancer - Crear J (Dove Medical Press, 2013)
Jara Crear, Kim M Kummer, Thomas J Webster School of Engineering, Brown University, Providence, RI, USA Abstract: Cervical cancer can be treated by surgical resection, chemotherapy, and/or radiation. Titanium biomaterials have been suggested as a tool to help in the local delivery of chemotherapeutic agents and/or radiation to cervical cancer sites. However, current titanium medical devices used for treating cervical cancer do not by themselves possess any anticancer properties; such devices act as carriers for pharmaceutical agents or radiation sources and may even allow for the growth of cancer cells. Based on studies, which have demonstrated decreased lung, breast, and bone cancer cell functions on nanostructured compared to nanosmooth polymers, the objective of the present in vitro study was to modify titanium to possess nanotubular surface features and determine cervical cancer cell adhesion after 4 hours. Here, titanium was anodized to possess nanotubular surface features. Results demonstrated the ability to decrease cervical cancer cell adhesion by about a half on nanotubular compared to currently used nanosmooth titanium (without the use of chemotherapeutics or radiation), opening up numerous possibilities for the use of nanotubular titanium in local drug delivery or radiation treatment of cervical cancer. Keywords: cervical cancer, titanium, nanotubular, cell density